Training of Mover Teachers in Improving the Quality of Learning in Kindergarten, Mallusetasi District - Fitri, Riskal; R, Nasaruddin; Imran, Muhammad Chairil; Nurhidayah, A. Resky; Ashar, Ashar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
A Mover teacher is a learning leader who plays an important role in educational transformation in Indonesia. This community service activity aims to improve teacher competence at TK District Mallusetasi in applying the concept of Mover teachers through comprehensive training. The method used is participatory training with an andragogy approach which includes interactive lectures, group discussions, teaching practice simulations, and continuous mentoring. The activity was carried out for three months involving 15 teachers from TK Kecamatan Mallusetasi. The instruments used included teacher competency tests, teaching practice observation sheets, and program evaluation questionnaires. The results of the activity showed a significant increase in teacher competence by 78.5% from pre-test to post-test scores. Teachers' ability to design child-centered learning increased from 65.2% to 89.7%. Innovative and collaborative learning practices also experienced substantial improvement. This activity has a positive impact on the quality of learning at TK Kecamatan Mallusetasi and can be a replication model for other similar schools.